Lipidomic chemotaxonomy aligned with phylogeny of Halobacteria - Yao, Wenyong; Zhang, Wan; He, Wei; Xiao, Wenjie; Chen, Yufei; Zhu, Yuanqing; Zheng, Fengfeng; Zhang, Chuanlun (Frontiers in Microbiology, 2023)
Archaea play an important role in global biogeochemical cycles and are considered ancestral to eukaryotes. The unique lipid composition of archaea, characterized by isoprenoid alkyl chains and ether linkage to glycerol-1-phosphate, offers valuable insights into archaeal phylogeny and evolution. However, comprehensive studies focusing on archaeal lipidomes, especially at the intact polar lipid level, are currently limited. Here, we built an in-house library of archaeal lipids by using highperformance liquid chromatography coupled with mass-spectrometry, which was integrated with bioinformatics and molecular network analyses. Seven halobacterial strains, representing three distinct orders, were cultured under identical conditions to investigate their lipidomes. A total of 162 features were identified, corresponding to 107 lipids that could be assigned to different strains. Clustering analyses of both core lipids and total lipids matched the phylogeny of Halobacteria at the order level. Notably, lipids such as triglycosyl diether-phosphatidyl acid and bis-sulfate glycosyl lipids were specific to particular groups and could serve as diagnostic intact lipid biomarkers for Halobacteria. Furthermore, the analysis of network-coordinated features facilitated the linkage of unknown lipid compounds to phylogeny, which promotes a lipidome to phylogeny matchup among three Haloferax strains, thereby expanding the knowledge of the halobacterial lipidome. Our study provides a comprehensive view of the lipidomes of the seven strains of Halobacteria and highlights the potential of lipidomics for studying archaeal phylogeny.